Acupuncture alleviates acute peritonitis: A case report. Issue 4 (April 2023) - Chen, Yun; Chen, Xiaoyan; Qian, Hong; Li, Biyi; Su, Xuan
Abstract: Many inflammatory and infectious entities can affect the peritoneum acutely, and patients with peritonitis often have painful expressions. Abdominal pain can be aggravated by coughing, breathing, and turning the body. Here we report the case of an 88-year-old patient with acute gastrointestinal perforation. The patient has been experiencing pain in the right lower abdomen, presenting persistent colic. The X-ray of abdomen and abdominal computed tomography showed perforation of digestive tract. In addition to the use of anti-infection and stomach protection agents, we use different analgesic injections, but the effect on reducing the pain was not obvious. After acupuncture treatment, the patient quickly relieved the pain of acute peritonitis in 1 minute. However, to our knowledge, there is few literature showing that acupuncture relieves preoperative opioid-induced hyperalgesia in patients with acute peritonitis. Based on this case, we suggest acupuncture as an option in the management of relieving the pain of acute peritonitis when opioid therapy is ineffective.